2020
DOI: 10.14743/apem2020.3.369
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based time evaluation of basic manual assembly tasks

Abstract: The paper presents a simple simulation model of the lifting procedure that can be used to predict the total time required for the sequence of basic manual assembly tasks depending on the various parameters of the load and with regard to the workers' health. The aim of the research is to determine the appropriateness of using simulation tool for (re)setting time standards for manual assembly tasks. An avatar in the simulation model performs sequences of tasks with a handling mass of up to 20.5 kg. The individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Poor instructions and procedures [42], task complexity [43], time pressure [28], workload [2], repetitive task [35,44], and multitasking [45][46][47][48].…”
Section: Task Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor instructions and procedures [42], task complexity [43], time pressure [28], workload [2], repetitive task [35,44], and multitasking [45][46][47][48].…”
Section: Task Factorsmentioning
confidence: 99%
“…Moreover, many studies focusing on human error have emphasized tool factors, such as using necessary and appropriate tools [36,39], and task factors, such as instructions and procedures [42], task complexity [43], time pressure [2], workload [2], and multitasking [45][46][47][48]. Human errors have been studied extensively, with many previous studies concentrating on organizational factors such as training [25], a lack of supervision, and avoiding the root cause of the error [39].…”
Section: Ranking Factors Influencing Hes Based On the Fuzzy Delphi Me...mentioning
confidence: 99%
“…As such, simulations are key to improve and evaluate system performance. The use of simulations in company practice can also bring us many other benefits, such as rationalising the number of workers at workplaces; accelerating material flows by adjusting routes; minimising the time needed to produce products at selected workplaces; detecting waste in production [15,16] or realised ergonomic analyses to improve satisfaction in the workplaces [17,18]. The simulations also allow optimisation of the manufacturing system in the context of a multi-objective optimisation problem [19].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have a team that work for this company and hold a position as transformer line production executives who are able to decide experiments and decisions for this research. The study showed methods for improving production processes by reducing cost, time and waste, instead of increasing budgets by applying industrial engineering tools and Lean manufacturing approach [19]. All operations and procedures of transformer production in the case study firm were analyzed by principles of Lean with the time study measurement of workers by MTM2 technique [20][21] [22].…”
Section: Introductionmentioning
confidence: 99%